A simple method for approximate estimation of the displacement response of base-isolated structures. (July 2022) - Yaghmaei-Sabegh, Saman; Jafari, Ebrahim; Neekmanesh, Shabnam
Abstract: The present study is a new attempt to provide a simple method for approximate estimation of the displacement response of base-isolated structures. For this purpose, first the accuracy of the existing methods which have been presented for base-isolated buildings is examined by comparison their estimations with the results of time history analyses of the 2, 4, 6, 8, 10 and 12 stories base-isolated models under 40 near-field and 40 far-field ground motion records. Then, a new method is proposed which is based on equivalent linear SDOF system with considering modified values of optimum damping ratio and effective period factor for base-isolated structures. The optimum damping ratio for base-isolated structures is obtained 31% and 23% for far- and near-field ground motion records, respectively. An effective period factor of 2.02 and 1.99 is extracted as a suitable value for obtaining the period of equivalent linear structure subjected to far- and near-field ground motion records, respectively. Results show that the proposed method not only has practically more simple procedure than the others, but also can provide reasonable estimates of the maximum nonlinear roof displacement of base-isolated structures subjected to an individual ground motion record. It's worth mentioning that most of the equivalent linearization methods presented in the past use displacement ductility ratio as a key parameter for estimating the nonlinear displacement of base-isolated structures while the proposed method doesn't need to such a parameter which cannot be easily predicted without performing nonlinear time history analysis. Therefore, as another attempt in this study, suitable approximate values of ductility ratio and other important coefficients are recommended for a number of existing approximate methods to improve their estimations for base-isolated structures.